The Good Left Undone : a novel - Trigiani, Adriana (New York : Dutton, an imprint of Penguin Random House LLC, 2022)
"From present day Viareggio to Glasgow during World War II, a multigenerational sweeping tale of love lost, family secrets, and reconciliation over decades from New York Times bestselling author Adriana Trigiani"--.